2006
DOI: 10.3748/wjg.v12.i38.6225
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer with a high serum IgG4 concentration

Abstract: Differentiation between autoimmune pancreatitis and pancreatic cancer is sometimes difficult. It has been reported that serum IgG4 concentrations are significantly elevated and particularly high (>135 mg/dL) in autoimmune pancreatitis. Measurement of serum IgG4 has become a useful tool for differentiating between autoimmune pancreatitis and pancreatic cancer. However, we present a 74-year-old female with a markedly elevated serum IgG4 (433 mg/dL) who underwent pancreaticoduodenectomy for pancreatic cancer. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 14 publications
1
62
0
3
Order By: Relevance
“…[9][10][11] Recent reports have shown destructive IgG4 lesions involving the maxillary sinus 12 and nasal septum, 13 both of which resolved after treatment with systemic corticosteroids. Gill et al reported salivary duct carcinoma arising in IgG4-related fibrosclerosis involving the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Recent reports have shown destructive IgG4 lesions involving the maxillary sinus 12 and nasal septum, 13 both of which resolved after treatment with systemic corticosteroids. Gill et al reported salivary duct carcinoma arising in IgG4-related fibrosclerosis involving the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…AIP patients frequently exhibit positive serologic antibodies, and elevated levels of γ-globulin or IgG. It has reported that elevated levels of the IgG4 were a sensitive and specific marker of AIP [36,37] ; however, elevated level of IgG4 seems nonspecific for AIP [13,38] and its role requires further study. In China, the determination of serum IgG4 level is still unavailable for most of hospitals, so we did not use it in our diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…El valor diagnóstico de la ecografía transabdominal es limitado dada su poca especificidad, observándose habitualmente un páncreas aumentado hipoecoico (44). No está claramente establecido el valor de la RNM con colangiopancreatografía (44,46); no obstante se ha constatado también un aumento difuso o localizado del páncreas con baja densidad en T1 y alta en T2 (Fig. 4A).…”
Section: Parénquima Pancreáticounclassified
“…5) (5,39,40). Con la progresión de la enfermedad, sin tratamiento, este estrechamiento tiende a extenderse a toda la extensión del conducto (46). También ha sido observado que distalmente al estrechamiento raramente existe una dilatación significativa del conducto, a diferencia de lo que comúnmente existe en la pancreatitis crónica etílica o el cáncer de páncreas (25,32,44,45).…”
Section: Conductos Pancreáticosunclassified
See 1 more Smart Citation